Regulation of TNF-α mRNA expression in endometrial cells by TNF-α and by oestrogen withdrawal - Tabibzadeh, Siamak; Satyaswaroop, P. G.; Wolff, Michael von; Strowitzki, Thomas (Molecular human reproduction, 1999)
Abstract. During each menstrual cycle, the human endometrium undergoes a series of orchestrated and well controlled changes in anticipation of the arrival of th
Gesehen am 27.11.2020